2008
DOI: 10.1096/fj.08-108712
|View full text |Cite
|
Sign up to set email alerts
|

Real‐time imaging ofLeishmania mexicana‐infected early phagosomes: a study using primary macrophages generated from green fluorescent protein‐Rab5 transgenic mice

Abstract: The small GTPase Rab5 is a key regulator of endosome/phagosome maturation and in intravesicular infections marks a phagosome stage at which decisions over pathogen replication or destruction are integrated. It is currently unclear whether Leishmania‐infected phagosomes uniformly pass through a Rab5+ stage on their intracellular path to compartments with late endosomal/ early lysosomal characteristics. Differences in routes and final compartments could have consequences for accessibility to antileishmanial drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 54 publications
3
19
1
Order By: Relevance
“…of infection, amastigotes, but not promastigotes, retained Rab5 staining. These results agree with studies in L. mexicana infection, in which amastigotes retain Rab5 longer than promastigotes, i.e., about one and two minutes, respectively [48]. The ability of parasites to hold on longer to Rab5 is LPG mediated, as LPG KO promastigotes retained Rab5 similar to amastigotes.…”
Section: Discussionsupporting
confidence: 90%
“…of infection, amastigotes, but not promastigotes, retained Rab5 staining. These results agree with studies in L. mexicana infection, in which amastigotes retain Rab5 longer than promastigotes, i.e., about one and two minutes, respectively [48]. The ability of parasites to hold on longer to Rab5 is LPG mediated, as LPG KO promastigotes retained Rab5 similar to amastigotes.…”
Section: Discussionsupporting
confidence: 90%
“…Taken together, these results unambiguously prove that Leishmania inhibits its transport to the lysosomes to survive in human macrophages. However, our results have also shown that Leishmania containing PV in mouse macrophages does not recruit and retain Rab5a after 24 h of infection whereas Leishmania containing PV in mouse macrophages is shown to recruit Rab5 in early time point of infection [52]. This is possibly due to the fact that Leishmania infection does not overexpress Rab5a in mouse macrophages.…”
Section: Discussionmentioning
confidence: 75%
“…Fusion between PVs before 12 h of infection was seldom observed. Indeed, Lippuner and colleagues found that a minority of Rab5-positive L. mexicana PVs fuse with each other in the first hours of intracellular infection [30]. The fusion between L. amazonensis PVs did not contribute to sustain PV enlargement because fused PVs regained their dimensions, a process probably related to compensatory membrane recycling.…”
Section: Discussionmentioning
confidence: 99%